Association between DNA content and tumor suppressor gene expression and aggressiveness of atypical teratoid/rhabdoid tumors - DAĞÇINAR, ADNAN (SPRINGER-VERLAG, 2002)
Objects: Atypical teratoid/rhabdoid tumors (AT/RT) are aggressive neoplasms that afflict infants and young children. The objective of this retrospective study was to determine the association between DNA content (DNA ploidy, cell cycle analysis), tumor suppressor gene (p53, pRb, p16, and MMAC/PTEN) expression and the biologic aggressiveness of these tumors. Methods: Eight tumors from 7 patients (1 girl, 6 boys; median age 4+/-6.7 months) were studied. Two patients had DNA aneuploidy and 5 patients manifested diploid DNA content at diagnosis. The proliferative index of the tumors ranged from 10% to 28% (median, 12+/-6.4%). The single tumor with a low proliferative index (i.e., <10%) was aneuploid. Immunohistochemical evaluation of p53, pRb, p16, and MMAC/PTEN expression patterns showed that most of the tumors contained more cells with abnormal pRb and p16 expression than cells with abnormal p53 and MMAC/PTEN expression. Expression of tumor suppressor genes, however, was inhomogeneous. Conclusion: Our findings led us to conclude that AT/RT of childhood is characterized by a high proliferative index and DNA aneuploidy. The high expression of abnormal pRb and p16 and the low expression of abnormal p53 and MMAC/PTEN indicate alteration of the G1-to-S phase step in the cell cycle, which could be an explanation for the aggressive nature of these tumors.
Keywords: atypical teratoid/rhabdoid tumor; tumor suppressor genes; MMAC/PTEN; p16; pRb; p53; HUMAN BRAIN-TUMORS; GLIOBLASTOMA-MULTIFORME; RHABDOID TUMOR; PROGNOSTIC-SIGNIFICANCE; TERATOID TUMOR; INFANCY; CHILDHOOD; P53; DEFINITION; MMAC/PTEN